Observance with the Principles of Fair Trial in Administrative and Disciplinary Violations; Iran and England with Emphasis on the Non Bis in Idem Principle - Hakime Farnam; Mohammad Mahdavisabet; , Mohammad Ashouri; Ali Saffary (پژوهشهای حقوقی)
The principle ne bis in idem, as one of the principles of fair proceedings, is rooted in the acceptance of the negative effect of foreign criminal sentences and is derived from the most important goals of international criminal law, i.e. preventing re-punishment of the accused for a single criminal act. This prohibition is a reminder of an important rule in the Criminal proceedings are called the validity of the judged criminal case in the criminal court. Even though administrative and disciplinary violations have significant differences with criminal offenses in terms of their nature, sources and examples, but in terms of comparison, their similarities, especially in predicting the guarantee of repressive executions, are significant, as they cannot be divided into two completely independent areas. On the other hand, entering the discussion of the criminal matters has made it more necessary to pay attention to these similarities, which are the basis for the perpetrator to enjoy the guarantees of fair trial principles, both in crimes and in administrative and disciplinary violations. In Iran, in relation to administrative and disciplinary violations, some of the principles of fair proceedings, especially the important principle ne bis in idem, are not only not observed, but according to Article 19 of the Administrative Violations Law 1372, it is even stipulated against it. Therefore, in this article, while comparing the crimes and violations, with the assumption that the English criminal system is a good model in this field, researcher has also briefly discussed the procedure of the administrative courts of this country. The study method in this article is analytical-descriptive and based on the review of related domestic and foreign texts.